Variability of baseline vehicle control among sober young adult cannabis users: A simulator-based exploratory study. (25th November 2019) - Brown, Timothy; Banz, Barbara; Li, Kaigang; Camenga, Deepa; Vaca, Federico; Gaffney, Gary; Milavetz, Gary
Abstract: Objective: The objective of this study was to compare the variability in vehicle control for sober young adult drivers (18–23 years old) who either use cannabis but are not acutely exposed or do not use cannabis. Methods: The data analyzed in the study were from 4 prospective driving simulation studies (completed at the National Advanced Driving Simulator at the University of Iowa) that examined vehicle control metrics in cannabis users and nonusers across high-fidelity simulated urban, interstate, and rural driving environments. Data were collected for segments of consistent driving environments including urban driving, urban curves, interstate, interstate curves, dark rural, and rural straight. Dependent measures included measures of lateral and longitudinal vehicle control. Results: Thirty out of 72 (12 users and 18 nonusers) met the age requirements for inclusion in the analysis. Between the cohorts, we identified differences in lateral and longitudinal driving performance. For lateral control there were no observed effects on variability in lane keeping. Cannabis users exhibited lower frequency steering and fewer and less variable steering reversals compared to nonusers. For longitudinal control, cannabis users drove slower than nonusers and more accelerator pedal holds and a lower accelerator pedal reversal rate were observed. Conclusions: Young adult drivers who use cannabis in our study drove slower and produced significantly less frequent steering and accelerator pedal inputs than drivers who did not use cannabis. This suggests that lasting effects of cannabis use persist and may lead to detrimental driving behaviors even after intoxication has subsided. These findings have implications for legislation in support of legalizing cannabis because sober cannabis-using drivers may still be a public health concern. Further study is needed to evaluate whether these differences persist even with longer term abstinence and whether differences are found in other age demographics.